A highly contorted push–pull naphthalenediimide dimer and evidence of intramolecular singlet exciton fission. Issue 39 (28th September 2022) - Bansal, Deepak; Kundu, Arup; Singh, Vijay Pal; Pal, Arun K.; Datta, Ayan; Dasgupta, Jyotishman; Mukhopadhyay, Pritam
Abstract : We report for the first-time intramolecular singlet fission (SF) in the naphthalenediimide (NDI) scaffold constrained in a cyclophane architecture, while individually the NDI units does not satisfy the requisite energy criterion for SF. Abstract : Singlet fission is a process by which two molecular triplet excitons are generated subsequent to the absorption of one photon. Molecules that enable singlet fission have triplet state energy at least half of the bright singlet state energy. This stringent energy criteria have challenged chemists to device new molecular and supramolecular design principles to modulate the singlet–triplet energy gap and build singlet fission systems from a wide range of organic chromophores. Herein, we report for the first time intramolecular singlet fission in the seminal naphthalenediimide (NDI) scaffold constrained in a push–pull cyclophane architecture, while individually the NDI chromophore does not satisfy the energy criterion. The challenging synthesis of this highly contorted push–pull cyclophane is possible from the preorganized pincer-like precursor. The special architecture establishes the shortest co-facial NDI⋯NDI contacts (3.084 Å) realized to date. Using broadband femtosecond transient absorption, we find that the correlated T–T pair forms rapidly within 380 fs of photoexcitation. Electronic structure calculations at the level of state-averaged CASSCF (ne, mo)/XMCQDPT2 support the existence of the multi-excitonic T–T pair state, thereby confirming the first example of singlet exciton fission in a NDI scaffold.